"Rur-Ban" Rail-Trail Business Impact: Case Study of the Mon River Trails System in West Virginia, USA. (June 2018) - Abildso, Christiaan; Bias, Tom; Coffman, Jessica
Abstract : Background: The Mon River Trails System (MRTS) is a network of 48 miles of trails in north central West Virginia that has been in operation in-whole or in-part since 1998. It runs through the rural core city of Morgantown - a densely populated town with a large university and strong economy that is surrounded by an historically rural landscape and culture (a "rur-ban" area). Rail-trails have a multitude of potential community benefits, including economic - expanded tourism, redevelopment of blighted industrial areas, and the creation of a sense of place. As rural trails such as the MRTS mature, localities are working creatively to spur investment along and near these trails. Much can be learned for future long-distance trail projects from mature trails such as the MRTS that traverse isolated rural to large rural core town areas. Thus, the purpose of this project was to conduct a case study assessment of the business impact of the MRTS and identify the lessons learned that may be applicable in other rural core settings. Methods: Our study was guided by six research questions which will be described during the presentation. We collected the following data: Surveys (n=61) from businesses within four blocks of the trail; Interviews of 17 business owners that opened since trail construction; Interviews of 2 business owners that located their business on the trail after it was built but did not stay; Assessed values of properties within one block of the trail, dating back to pre-construction (1994–2016); Focus group with local government, trail advocacy, and visitors' bureau representatives; and Focus group with directors & county officials in charge of three local Tax Increment Financing (TIF) districts. Results: In combination, the multiple sources of data highlight three key points: Unlike many other trails studied to date, the MRTS is a local transportation and recreation hub, not a tourism-driven trail; The trail has a multitude of secondary community benefits, including social space, an event location for non-profits, resident and workforce recruitment and retention; and Median property values (including land and building) along the trail have increased 172.6% since 2004; relative to a 68.3% in countywide median home values. Conclusions: Practice Implications: Proper trail development requires collaborative public-private planning, creative funding, and incentives for economic development from the outset. More details about the benefits of the MRTS and implications, including policy and economic development suggestions, will be presented.